2022
DOI: 10.1186/s42047-022-00112-y
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted tumor grading, validation of PD-L1 scoring, and quantification of CD8-positive immune cell density in urothelial carcinoma, a visual guide for pathologists using QuPath

Abstract: Background Advances in digital imaging in pathology and the new capacity to scan high-quality images have change the way to practice and research in surgical pathology. QuPath is an open-source pathology software that offers a reproducible way to analyze quantified variables. We aimed to present the functionality of biomarker scoring using QuPath and provide a guide for the validation of pathologic grading using a series of cases of urothelial carcinomas. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Using QuPath, no significant difference was found between the automated image analysis scoring algorithm and pathologist HNSCC CPS scores 10 or in urothelial carcinomas. 21 Similarly, no significant difference between the automated FDA-cleared Aperio Imagescope IHC Membrane Image Analysis software scoring algorithm and pathologist scoring in gastric cancer was found. 26 Likewise, no significant difference between the automated image analysis scoring algorithm and pathologist scores in pancreatic cancer was obtained using PyRadiomics software.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using QuPath, no significant difference was found between the automated image analysis scoring algorithm and pathologist HNSCC CPS scores 10 or in urothelial carcinomas. 21 Similarly, no significant difference between the automated FDA-cleared Aperio Imagescope IHC Membrane Image Analysis software scoring algorithm and pathologist scoring in gastric cancer was found. 26 Likewise, no significant difference between the automated image analysis scoring algorithm and pathologist scores in pancreatic cancer was obtained using PyRadiomics software.…”
Section: Discussionmentioning
confidence: 96%
“…An advantage of using semi-automated image analysis scoring over conventional scoring is that it measures DAB color staining in the entire annotated tumor region as a continuous variable with a single density score in comparison to pathologists scoring which provides only a visual estimate of PD-L1 expression in the same tumor region. 21 23 Another study suggested that the automated image analysis of the Dako 22C3 IHC assay yielded slightly lower percentages of positive cells compared with conventional scores. 24 This agrees with our results for DLBCL using the HSB method and for HNSCC using both RGB and HSB methods.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring of PD-L1 in non-small cell lung cancer and urothelial carcinomas by QuPath has already been validated and has shown a good reliability [ 16 , 17 ]. So, we decided to evaluate membranous staining of PD-L1 in an automated, quantitative, objective, and standardized manner by using the analysis software QuPath v3.4 (Open Software for Bioimage Analysis) after scanning the slides with 200× magnification (Nanozoomer HT2.0, Hamamatsu Photonics, Hamamatsu, Japan) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Probably the most relevant key point of QuPath is linked with its inherent flexibility, which is demonstrated by its application to a wide range of human pathology research and clinical areas. QuPath has been successfully utilized for computer-assisted tumor grading, PD-L1 scoring, and quantification of CD8positive immune cell density in urothelial carcinoma [36] and to detect and measure cell morphology. Another study [37] used QuPath to identify MLH1-deficient inflammatory bowel disease-associated colorectal cancers from tissue microarray.…”
Section: Qupathmentioning
confidence: 99%
“…From this review, it emerges that machine learning algorithms have improved diagnostic accuracy by providing an excellent tool for the identification of anomalies in whole slide images (WSIs) that may be missed, in some cases, by human pathologists. For example, recent studies have demonstrated improved accuracy in tumor grading and biomarker scoring, such as PD-L1 and CD8+ cell density measurements in cancer tissues [36,37]. The adoption of these tools drastically reduced the time for manual review, allowing pathologists to focus on those cases that are inherently more complex [37,38].…”
Section: Main Findings and Limitationsmentioning
confidence: 99%